2004
DOI: 10.1007/978-3-540-24727-2_10
|View full text |Cite
|
Sign up to set email alerts
|

LTL over Integer Periodicity Constraints

Abstract: Abstract. Periodicity constraints are used in many logical formalisms, in fragments of Presburger LTL, in calendar logics, and in logics for access control, to quote a few examples. In the paper, we introduce the logic PLTL mod , an extension of Linear-Time Temporal Logic LTL with past-time operators whose atomic formulae are defined from a first-order constraint language dealing with periodicity. Although the underlying constraint language is a fragment of Presburger arithmetic shown to admit a pspace-complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 54 publications
1
54
0
1
Order By: Relevance
“…We have shown that this task is simple in the setting of Pnueli's LTL. However, for some relevant richer logics, like real-time logics [11] or logics interpreted over the integers [5], this task is considerably more involved [4]. Nevertheless, as the approach given for LTL suggests, there is a typical pattern for deriving those functions, which we describe in this section.…”
Section: Monitors Via the Automata-theoretic Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…We have shown that this task is simple in the setting of Pnueli's LTL. However, for some relevant richer logics, like real-time logics [11] or logics interpreted over the integers [5], this task is considerably more involved [4]. Nevertheless, as the approach given for LTL suggests, there is a typical pattern for deriving those functions, which we describe in this section.…”
Section: Monitors Via the Automata-theoretic Approachmentioning
confidence: 99%
“…In the setting of the real-time logic TLTL [11], an event-clock automaton is constructed accepting precisely the models of the formula at hand. In the setting of Demri's PLTL mod [5], words over an infinite alphabet (representing integer valuations) are abstracted to words of a finite alphabet and a suitable construction of a Büchi automaton accepting these symbolic evaluations is provided.…”
Section: Monitors Via the Automata-theoretic Approachmentioning
confidence: 99%
See 3 more Smart Citations